Membentuk Karakter Kemandirian Belajar Siswa Melalui Metode Fingermathic Di SD N 010246 Banjar - Sirait, Syahriani; Sari, Putri Lidiana Permata (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
This research aims to examine the effectiveness of the Fingermathic method in forming students' independent learning character. This method is applied in mathematics learning in elementary schools with a focus on the use of fingers as a tool for visualizing arithmetic operations. The research involved students as test subjects who were assessed through an evaluation questionnaire on various aspects of the characteristics of independent learning. The results of the analysis show that the Fingermathic method can increase students' learning initiative and self-confidence, although more attention is still needed on the aspects of setting targets, overcoming difficulties, and evaluating learning outcomes. The conclusions of this research provide a basis for further development in designing learning strategies that support the formation of students' independent learning character at the elementary school level.            Keywords: student character; learning independence; fingermathic